Body weight and mortality in takotsubo syndrome: insights from the International Takotsubo (InterTAK) registry. (3rd October 2022) - Stahli, B; Cammann, V L; Schindler, M; Schweiger, V; Szawan, K A; Niederseer, D; Wurdinger, M; Schonberger, A; Schonberger, M; Koleva, I; Mercier, J C; Petkova, V; et al.
Abstract: Background/Introduction: The obesity paradox has been described in different cardiovascular conditions. Data on the association between obesity and outcomes in patients with Takotsubo syndrome (TTS) are lacking. Purpose: The aim of this study was to determine the relation of body weight to mortality in TTS patients. Methods: Patients enrolled in the International Takotsubo (InterTAK) Registry from January 2011 to July 2021 and with available data on BMI were included in the analysis. Patients were stratified according to BMI (underweight, <18.5 kg/m 2 ; normal weight, 18.5–24.9 kg/m 2 ; overweight, 25.0–29.9 kg/m 2 ; obese, 30.0–34.9 kg/m 2 ; and very obese, ≥35.0 kg/m 2 ). The primary endpoint was mortality at 1 year. Results: Of the 2'707 patients, 222 (8.2%) were underweight, 1340 (49.5%) of normal weight, 759 (28.0%) overweight, 268 (9.9%) obese, and 118 (4.4%) very obese. Mortality at 1 year as a function of BMI with 95% confidence interval is given in Figure 1. Mortality at 1 year was 11.3%, 6.9%, 5.5%, 4.9%, and 9.3% in underweight, normal weight, overweight, obese, and very obese patients (p=0.02, Figure 2). Being overweight or obese was significantly associated with a lower mortality at 1 year (HR 0.70, 95% CI 0.51–0.96, p=0.03), and associations remained significant after multivariable adjustments (adjusted HR 0.67, 95% CI 0.46–0.97, p=0.03). Associations were observed when including patients without emotional stressors (adjusted HR 0.64, 95% CI 0.43–0.94, p=0.02), but not when including those with emotional stressors (adjusted HR 1.14, 95% CI 0.30–4.27, p=0.85). Conclusion: A U-shaped mortality curve across BMI categories was observed in TTS patients, with lowest mortality rates in obese patients. These observations provide first evidence for the existence of the obesity paradox in TTS. Funding Acknowledgement: Type of funding sources: Foundation.